Marine microalgae Schizochytrium demonstrates strong production of essential fatty acids in various cultivation conditions, advancing dietary self-sufficiency - Literáková, Petra; Zavřel, Tomáš; Búzová, Diana; Kaštánek, Petr; Červený, Jan (Frontiers in Nutrition, 2024)
Polyunsaturated fatty acids (PUFA) provide numerous health benefits and humans have to obtain essential fatty acids (FA), such as ω-3 and ω-6, from their diet. At present, the primary source of essential fatty acids for human consumption is fish oil, but its production is no longer sustainable. An alternative approach is to produce PUFAs through marine microalgae. Many algae strains can accumulate high concentrations of PUFAs including essential FAs. Numerous aspects of PUFA production by microalgae, however, are yet to be fully explored, and their current production outputs are frequently suboptimal.Within this study, the production of biomass and selected ω-3 PUFAs was optimized in two strains of algae, Schizochytrium marinum AN-4 and Schizochytrium limacinum CO3H. The optimization concerned a broad range of cultivation conditions, including pH, temperature, stirring intensity, nutrient concentrations, and their selected combinations. Both strains were found to grow well at pH levels as low as 4.5, which has the potential to reduce bacterial contamination and facilitate the use of industrial waste products as a substrate supplement. Intensive stirring was found to be necessary for rapid biomass accumulation, but it also caused cell disruption during the lipid accumulation phase. Docosahexaenoic acid (DHA) yield was independent of cultivation temperature within the range of 28-34 °C.Both tested strains were capable of achieving high cell densities (up to 9 g L -1 ) and stable DHA production (average around 0.1 g L -1 d -1 ) under diverse cultivation conditions and nutrient concentrations. The minimal nutrients required for stable DHA production included standard sea salt, glucose or glycerol, and yeast extract. Considering the robust production of both investigated Schizochytrium strains and the development of a new minimal culturing medium with reduced ionic strength and antibacterial pH, these findings can potentially boost industrial-scale production and make it more economically viable. Additionally, they may also pave the way for the production of essential fatty acids on a smaller scale in a domestic setting.